How Robust Is the Apparent Break‐Down of Northern High‐Latitude Temperature Control on Spring Carbon Uptake?. Issue 7 (29th March 2021) - Joyce, Peter; Brienen, Roel; Buermann, Wolfgang; Wilson, Chris; Chipperfield, Martyn P.; Claret, Mariona; Gloor, Manuel
Abstract: Vegetation growth in northern high‐latitudes during springtime is strongly temperature limited, and thus anomalously warm springs are expected to result in an increased drawdown of carbon dioxide (CO2 ). However, a recent analysis of the relationship between spring temperature anomalies and atmospheric CO2 anomalies at Point Barrow, Alaska, suggests that the link between spring carbon uptake by northern ecosystems and temperature anomalies has been weakening over recent decades due to a diminishing control of temperature on plant productivity. Upon further analysis, covering the 1982–2015 period, we found no significant change in the relationship between spring vegetation productivity derived from remote sensing data and air temperature. We showed that a reduction in spatial coherence of temperature anomalies, alongside a significant sensitivity to atmospheric transport, is likely responsible for the apparent weakening. Our results, therefore, suggest that spring temperature remains as an important control of northern high‐latitude CO2 uptake. Plain Language Summary: The timing of the vegetation growing season is strongly linked to the quantity of carbon dioxide (CO2 ) absorbed each year, however, it is unclear how this will evolve. The spring zero crossing (SZC) of atmospheric CO2 is an indicator of how early the growing season starts. This is because the growing season is characterized by a significant photosynthetic drawdown of CO2 by vegetation. This quantity has historically been strongly controlled by temperature in northern high‐latitude ecosystems. A recent study analyzed surface CO2 data at a site in Alaska and suggested that this control has broken down. We show here, using satellite‐based vegetation data, that there has been no change in the control of temperature on vegetation productivity across the high northern latitudes. We then demonstrate that the temperature anomalies became more spatially variable across the northern high latitudes in recent decades and that variations in atmospheric circulation lead to different regions of influence over the Alaskan CO2 site. These influences play a key role in the year‐to‐year variability of the SZC and its relationship with temperature. Our study demonstrates that the control of temperature on the year‐to‐year variations in the timing and magnitude of spring CO2 uptake has remained strong. Key Points: No significant change in the overall temperature sensitivity of high northern latitude spring greenness in the past 40 years Decreased spatial coherence of spring temperature anomalies has increased the influence of atmospheric transport on surface CO2 data Temperature sensitivity of spring carbon uptake remains strong when accounting for atmospheric transport